Jude the Obscure - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 1994)
"Jude the Obscure" by Thomas Hardy is a novel published in 1895. It follows Jude Fawley, a working-class stonemason who dreams of becoming a scholar at Christminster. His ambitions become entangled with his passionate but troubled relationship with his cousin, Sue Bridehead. Through failed marriages, social ostracism, and personal tragedy, the novel explores the crushing weight of Victorian society's institutions$1 (Bparticularly marriage, religion, and class barriers$1 (Bon those who dare to defy convention. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Jude_the_Obscure
Release date is 1994-08-01
John Hamm. Revised by Joseph E. Loewenstein, M.D.
Keywords: Adultery -- Fiction; Didactic fiction; Love stories; Illegitimate children -- Fiction; Wessex (England) -- Fiction; Stonemasons -- Fiction; Children -- Death -- Fiction; Unmarried couples -- Fiction